2019
DOI: 10.3389/fpls.2019.00129
|View full text |Cite
|
Sign up to set email alerts
|

Crassulacean Acid Metabolism Abiotic Stress-Responsive Transcription Factors: a Potential Genetic Engineering Approach for Improving Crop Tolerance to Abiotic Stress

Abstract: This perspective paper explores the utilization of abiotic stress-responsive transcription factors (TFs) from crassulacean acid metabolism (CAM) plants to improve abiotic stress tolerance in crop plants. CAM is a specialized type of photosynthetic adaptation that enhances water-use efficiency (WUE) by shifting CO 2 uptake to all or part of the nighttime when evaporative water losses are minimal. Recent studies have shown that TF-based genetic engineering could be a useful approach for im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 79 publications
(144 reference statements)
0
19
0
Order By: Relevance
“…In comparison with C 3 species, changes in the expression of a large number of protein-encoding genes were also revealed in other comparative analyses of constitutive CAM plant species such as Agave (Abraham et al , 2016; Yin et al , 2018) and Ananas comosus (Ming et al , 2015). Additionally, many genes, including transcription factors, are potentially involved in CAM induction in facultative CAM plants such as Mesembryanthemum crystallinum (Amin et al , 2019). Besides protein-encoding genes, microRNAs (miRNAs) are likely involved in CAM gene regulation (Wai et al , 2017).…”
Section: The Course Of Cam Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with C 3 species, changes in the expression of a large number of protein-encoding genes were also revealed in other comparative analyses of constitutive CAM plant species such as Agave (Abraham et al , 2016; Yin et al , 2018) and Ananas comosus (Ming et al , 2015). Additionally, many genes, including transcription factors, are potentially involved in CAM induction in facultative CAM plants such as Mesembryanthemum crystallinum (Amin et al , 2019). Besides protein-encoding genes, microRNAs (miRNAs) are likely involved in CAM gene regulation (Wai et al , 2017).…”
Section: The Course Of Cam Evolutionmentioning
confidence: 99%
“…Recently, Brilhaus et al (2016) and Maleckova et al (2019) identified candidate transcription factors potentially involved in the regulation of the C 3 -to-CAM transition in the facultative CAM species Talinum triangulare , which is capable of reversible transitioning from C 3 photosynthesis to weak CAM in response to drought stress. More recently, eight transcription factors were identified as potential candidates regulating the induction of CAM by water-deficit stress in another facultative CAM species, Mesembryanthemum crystallinum (Amin et al , 2019). These comparative genomics analyses of stress-induced CAM versus C 3 photosynthesis provide insights into the course of CAM evolution.…”
Section: Determination Of Gene Function Required For Cam Using Comparmentioning
confidence: 99%
“…Recent advances in the understanding of CAM gene expression lay the groundwork for potential genetic engineering of CAM to improve crop tolerance (e.g. Amin et al , 2019; Lim et al , 2019).…”
Section: Technological Advances That Can Facilitate Agricultural Prodmentioning
confidence: 99%
“…Furthermore, it is possible that the CAM also reduced the effects of water deficit in the absence of rainfall, due to the plants adapting to the stress caused by the lack of water. As discussed above, CAM plants close their stomata during the day to reduce water loss and open them at night to increase CO 2 fixation, which results in greater water use efficiency and therefore greater resistance to drought (AMIN et al, 2019).…”
Section: Reproductive Growth In the Ornamental Pineapplementioning
confidence: 99%